2019
DOI: 10.1016/j.cub.2019.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Learning a Spatial Task by Trial and Error in Drosophila

Abstract: Learning a Spatial Task by Trial and Error in Drosophila Highlights d Flies possess ''reward'' neurons with properties similar to those of the vertebrate MFB d Closed-loop stimulation of these neurons enables flies to learn a spatial task d Flies' learning is influenced both by vision and non-visual features in the arena d Learning is enabled by specific DA and ChAT neurons as well as MB and CX in the brain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
5
18
0
Order By: Relevance
“…Each fly experienced only one stimulation probability condition and all flies were initially loaded into the center of the arena. Similar to previous studies [28][29][30], we observed clear effects of the light stimulation on behavior.…”
Section: Place Preference Depends On Optogenetic Stimulation Probabilsupporting
confidence: 91%
See 3 more Smart Citations
“…Each fly experienced only one stimulation probability condition and all flies were initially loaded into the center of the arena. Similar to previous studies [28][29][30], we observed clear effects of the light stimulation on behavior.…”
Section: Place Preference Depends On Optogenetic Stimulation Probabilsupporting
confidence: 91%
“…Therefore, we concluded that flies respond to optical stimulation by stopping and reversing their walking direction (turning). This behaviour is similar to local searches [31] previously described as a behavioural response to rewarding stimuli [29,30] and suggested that the stimulation in our experiments was also rewarding.…”
Section: Optogenetic Stimulation Triggers Local Search Behavioursupporting
confidence: 90%
See 2 more Smart Citations
“…3), and protein hunger only starts to influence male food choice much later (Ribeiro and Dickson, 2010). It also needs to be taken into account that food association in the Panopticon is not formed with odours but with place, and associations of spatial features involve the central complex (Liu et al, 2006;Stern et al, 2019); it is equally possible that plastic changes in this structure contribute to the observed location preference. In a place learning assay, the unavoidability of an aversive heat stimulus can boost its reinforcing propensities (Sitaraman and Zars, 2010); it is feasible that the same is the case for unavoidable starvation.…”
Section: Discussionmentioning
confidence: 99%